1987
DOI: 10.5144/0256-4947.1987.41
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma: Dhahran Health Center Experience

Abstract: A total of 15 patients (5 males, 10 females) with multiple myeloma and light-chain disease were encountered in Dhahran Health Center during a 6-year period since November 1979. Patients' ages ranged from 45 to 82. Frequency of immunoglobulin G (IgG), immunoglobulin A (IgA) and light-chain secreting tumors in the group were similar to those in larger series. Based on the pretreatment clinical data, 14 of 15 patients (93%) had advanced tumor burden (clinical stage III) and 9 out of 15 (60%) were classified as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…No periods of observation were possible because most were in Stage II or III. Onder [3], in a report of a small group of cases with multiple myeloma from the Eastern Province of Saudi Arabia, also found that his patients presented at a relatively advanced stage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…No periods of observation were possible because most were in Stage II or III. Onder [3], in a report of a small group of cases with multiple myeloma from the Eastern Province of Saudi Arabia, also found that his patients presented at a relatively advanced stage.…”
Section: Discussionmentioning
confidence: 89%
“…It is more common in males than in females, and in the USA is twice as common in blacks in whom it represents 7.2% of malignancies [2]. The incidence in Saudi Arabia is still unknown and the only report, which concerned 15 patients seen at Dhahran Health Center, appeared in the Annals of Saudi Medicine three years ago [3].…”
Section: Accepted For Publication 12 December 1990mentioning
confidence: 99%